Mechanisms of abscisic acid-mediated control of stomatal aperture - Munemasa, Shintaro; Hauser, Felix; Park, Jiyoung; Waadt, Rainer; Brandt, Benjamin; Schroeder, Julian I (Current opinion in plant biology, 2015)
•ABA triggers a robust signal network that controls stomatal closing.•Guard cell ABA levels are controlled by biosynthesis, catabolism, and transport.•SnRK2s and CPKs are key for ABA activation of anion channels in guard cells.•PP2Cs downregulate both Ca2+-independent and Ca2+-dependent ABA signaling branches.•Multiple biotic signal inputs target ABA signaling in guard cells. Drought stress triggers an increase in the level of the plant hormone abscisic acid (ABA), which initiates a signaling cascade to close stomata and reduce water loss. Recent studies have revealed that guard cells control cytosolic ABA concentration through the concerted actions of biosynthesis, catabolism as well as transport across membranes. Substantial progress has been made at understanding the molecular mechanisms of how the ABA signaling core module controls the activity of anion channels and thereby stomatal aperture. In this review, we focus on our current mechanistic understanding of ABA signaling in guard cells including the role of the second messenger Ca2+ as well as crosstalk with biotic stress responses.